INTEGRASI KEPEMIMPINAN PENDIDIKAN DAN MANAJEMEN RISIKO DALAM PENGELOLAAN ARSIP GUNA MENINGKATKAN KEAMANAN SERTA AKSESIBILITAS ARSIP - Ariq Mahdavikia Rahman; Diah Utami; Dwi Arli Farhatun Khasanah; Nila Aisyah; Siswadi (STKIP Subang, 2026)
This study aims to analyze the integration of educational leadership and risk management in archival management to enhance the security and accessibility of archives. The method used is a literature study by reviewing various sources such as books, scientific journals, and relevant documents related to the research topic. The results of the study indicate that educational leadership plays a strategic role in formulating policies, fostering an archive-aware culture, and ensuring the systematic implementation of risk management. Risk management in archival practices includes the identification, analysis, and mitigation of risks such as data loss, archive damage, and digital security threats. The integration of educational leadership and risk management has proven to improve archive security while facilitating easier access to information. Therefore, visionary, adaptive, and technology-oriented leadership is required to support an effective and sustainable archival system.